Selective Stimulation of the Spinal Cord Surface Using a Stretchable Microelectrode Array - Meacham, Kathleen W.; Guo, Liang; DeWeerth, Stephen P.; Hochman, Shawn (Frontiers in Neuroengineering, 2011)
By electrically stimulating the spinal cord, it is possible to activate functional populations of neurons that modulate motor and sensory function. One method for accessing these neurons is via their associated axons, which project as functionally-segregated longitudinal columns of white- matter funiculi (i.e., spinal tracts). To stimulate spinal tracts without penetrating the cord, we have recently developed technology that enables close-proximity, multi-electrode contact with the spinal cord surface. Our stretchable microelectrode arrays (sMEAs) are fabricated using an elastomer polydimethylsiloxane (PDMS) substrate and can be wrapped circumferentially around the spinal cord to optimize electrode contact. Here, sMEAs were used to stimulate the surfaces of rat spinal-cords maintained in vitro, and their ability to selectively activate axonal surface tracts was compared to rigid bipolar tungsten microelectrodes pressed firmly onto the cord surface. Along dorsal column tracts, the axonal response to sMEA stimulation was compared to that evoked by rigid microelectrodes through measurement of their evoked axonal compound action potentials (CAPs). Paired t-tests failed to reveal significant differences between the sMEA’s and the rigid microelectrode’s stimulus resolution, or in their ranges of evoked CAP conduction velocities. Additionally, dual-site stimulation using sMEA electrodes recruited spatially-distinct populations of spinal axons. Site-specific stimulation of the ventrolateral funiculus—a tract capable of evoking locomotor-like activity—recruited ventral-root efferent activity that spanned several spinal segments. These findings indicate that the sMEA stimulates the spinal cord surface with selectivity similar to that of rigid microelectrodes, while possessing potential advantages concerning circumferential contact and mechanical compatibility with the cord surface.